Existe relação entre a cinemática da corrida e a função dos músculos do assoalho pélvico de mulheres corredoras? - Silva, Rafaela de Melo (2017)
Running is one of the most popular types of physical activity in the world and women are increasingly included in this sport. Strenuous physical exercise that increases intra-abdominal pressure can chronically overwhelm and damage the pelvic floor muscles, ligaments and fascia, and decrease the contraction force of the muscles. In the running, vertical reaction forces with the ground can increase between 1.6 and 2.5 times the body weight and the transmission of the shock between the feet and the ground can affect the mechanism of continence by changing the amount of force transmitted to pelvic floor muscles. Studies have shown that the prevalence of urinary incontinence in long-distance runners is 62.2%. It is important to investigate whether kinematic patterns are related to urinary loss because it is believed that the characteristics of the movements can increase the impact load on the lower extremities resulting in excessive overload on the pelvic floor muscles since it is a sport of high impact that involves landing. The aims of this study was to evaluate if pelvic floor muscle function is related to the weekly training load and kinematic variables of the running. A cross-sectional observational study. Sample consisting of 11 runners with athletic incontinence and 15 continents runners. On day 1, the maximum velocity test on the treadmill was performed using an incremental protocol. On day 1, the maximum velocity test on the treadmill was performed using an incremental protocol. After 48 hours, evaluation of the pelvic floor muscles was performed through the vaginal palpation graded by the Oxford Scale, perineometry and adapted pad test. Then, the kinematics of the race on the treadmill through a circuit cameras. For recording the images, the speed of the treadmill was set at 75% of the maximum speed obtained. The vertical displacement was measured in a posterior view during a complete gait cycle, the knee flexion during the load response phase, and the initial contact of the foot with the ground, both in the right lateral view. The vaginal squeeze pressure obtained by the group of continents (45,10(20,74)) was higher when compared to the incontinent group (38,94(31,08)), but without statistically significant difference (p=0,55). There was an association between weekly training load and urine loss, suggesting that women who lose urine greater distance run per week. No associations were found between urine loss and kinematic variables. No relationship was found between the strength of the pelvic floor muscles and the vertical displacement, knee flexion and ground attack. The weekly training load seems to be associated with lower strength of the pelvic floor muscles.